Predictor variables of socio-emotional competence in pre-service early childhood and primary teachers - Romero-García, Carmen; Buzón-García, Olga; Sacristán San Cristóbal, Mara (Revista de Investigación Educativa, 2026)
Developing their socio-emotional competence makes a significant contribution to teachers’ well-being, which is key to effective education. Identifying which teacher characteristics are associated with this competence is essential when designing intervention programmes to foster its development. This study employs a multivariate model to examine whether the variables gender, teaching experience, and self-efficacy have a statistically significant effect on the level of pre-service teachers’ socio-emotional competence. A total of 700 students enrolled in the Early Childhood and Primary Education Degree programmes during the 2023/24 academic year at the International University of La Rioja took part in the study. A gender difference was observed in certain socio-emotional skills, with women scoring higher in some categories. The results indicate that teaching experience is associated with a decrease in most subscales of socio-emotional competence during the first three years of professional practice, after which a progressive increase in these competencies is observed. Among the variables analysed, teachers’ self-efficacy regarding teaching and learning strategies showed the strongest statistical association with socio-emotional competence, with significant and substantial effects on virtually all subscales. These findings have important implications for educational practice. They underscore the need to promote training programmes aimed at strengthening teachers’ self-efficacy as a means to support the socio-emotional development of educators.
Variables predictoras de la competencia socioemocional en futuros docentes de infantil y primaria
El desarrollo de la competencia socioemocional contribuye de forma significativa al bienestar del docente, lo que resulta clave para educar de forma eficaz. Determinar qué características de la persona docente se relacionan con esta competencia es clave cuando se diseñan programas de intervención para su desarrollo. En este trabajo se utiliza un modelo multivariante para analizar si las variables género, experiencia docente y autoeficacia tienen un efecto estadístico significativo sobre el nivel de competencia socioemocional. En el estudio participaron 700 estudiantes que cursaron los Grados de Maestro en Educación Infantil y Primaria durante el curso 2023/24, en la Universidad Internacional de La Rioja. Se evidenció una diferencia de género en algunas habilidades socioemocionales, con puntuaciones superiores en las mujeres. Los resultados indicaron que la experiencia docente se asocia con una disminución en la mayoría de las subescalas de la competencia socioemocional durante los primeros tres años de ejercicio, tras lo cual se produce un aumento progresivo en dichas competencias. Entre las variables analizadas, la autoeficacia docente para las estrategias de enseñanza y aprendizaje presentó una asociación estadística superior con la competencia socioemocional, con efectos significativos e importantes en prácticamente todas las subescalas. Estos resultados tienen importantes repercusiones para la práctica educativa. Subrayan la importancia de promover programas formativos orientados a fortalecer la autoeficacia docente como medio para favorecer el desarrollo socioemocional del profesorado.
Keywords: socio-emotional competence; self-efficacy; teaching experience; pre-service teachers; competencia socioemocional; autoeficacia; experiencia docente; futuros docentes